Juventude brasileira e política: uma análise da Revista MTV - Ribeiro, Julia Nepomuceno (2007)
Politics has become apparently distant reality for Brazilian youth currently and the importance of mass communication in the democratic process that has become even more evident, has led us to question not only the means by which young people approach politics but also the role of the media within this process. Thus, the objective of this work is to analyze how the MTV Magazine ( Revista MTV), a means of mass communication aimed at a young public, approaches politics in its reports and how it seeks to promote knowledge of specific current issues which may be used as an indicator that the relationship between youth and politics definitely does not happen inside the parties and labor unions themselves but in more fragmented specific movements, for identity build-up, for individual actions. Using a methodology that permitted the selection and identification of the theme, eight reports and two columns which addressed the above topics were selected from the fifteen issues of the MTV Magazine that were analyzed. The study revealed the magazine s stance in relation to politics and its concern for the development of young people s responsibility regarding certain topics and consequently, which possibilities for action and attitude they may have